Interrelationships among egg weight, hatchability, chick weight, post-hatch performance and rearing method in broiler breeders - RAJU, M V L N; CHAWAK, M M; PRAHARAJ, N K; RAO, S V R; MISHRA, S K (The Indian Journal of Animal Sciences, 2013)
Hatching eggs, from 2 broiler lines, categorised into 4 groups, viz. up to 60g (A), 60.1-65g (B), 65.1-70g (C) and above 70g (D), were incubated after being stored for 0-9 days at 10-15 oC. The hatchlings of each group were reared either separately or in mixed group together with those of other groups to assess their performance till 6 weeks of age. While fertility and percent hatch weight remained unaffected by egg size, hatchability decreased with increasing egg weight. Correlation coefficient between egg weight and body weight at all ages of measurement was positive. Day-old chick weight increased significantly (P